Hypotensive effect of Centella asiatica L. extract in acute Angiotensin II-induced hypertension: Centella asiatica extract and its effects on hypertension - Mohebbati, Reza; Kamkar-Del, Yasamin; Kazemi, Farzaneh; Rakhshandeh, Hasan; Shafei, Mohammad Naser (Iranian Journal of Pharmaceutical Sciences, 2020)
Centella asiatica L. (C.asiatica) is a plant with a hypotensive effect. Since this effect has several mechanism(s), therefore in the current study we investigated the effects of hydroalcoholic extract of C.asiatica on cardiovascular parameters in acute hypertensive rats. Animals were divided into four groups; 1) control, 2) Angiotensin II (AngII) that received (50 ng/kg) intravenously (i.v.), 3 and 4) two groups of C.asiatica extract (CA100, and CA200 mg/kg). In treated groups, 30 min after injection of the extract, AngII was injected. Cardiovascular parameters were recorded by the power lab system after the cannulation of the femoral artery. The maximum changes (Δ) of systolic blood pressure (SBP), mean arterial pressure (MAP), and heart rate (HR) were calculated and used for statistical analysis. In the AngII group, ΔSBP and ΔMAP significantly increased compared to the control group. The HR also decreased compared to the control group but it was not significant. In CA100+AngII group ΔSBP and ΔMAP significantly decreased compared to the AngII. The use of these doses of CA with AngІІ compared to AngІІ alone had a significant effect on the HR. In CA200+AngII group ΔSBP and ΔMAP significantly decreased compared to the AngII. The change of HR in this dose was not significant to the AngII. In a recent study, we concluded that C.asiatica decreased the cardiovascular responses in hypertensive rats received AngII. Also between two doses of C.asiatica did not observe any significant difference. Therefore, one of the most important hypotensive mechanism(s) of the considered plant can be the effect on Renin-angiotensin system.